Analisis Pengaruh Pertumbuhan Pembiayaan Modal Kerja, Investasi dan Konsumsi Pada Perbankan Umum Syariah Terhadap Pertumbuhan Produk Domestik Regional Bruto (PDRB) Kalimantan Barat Periode 2009-2013 - Hayet, Hayet (Fakultas Ekonomi dan Bisnis, UNTAN, 2016)
Islamic banking has an important role in stimulating the economy because of the intermediaryfunction performed. Improved economy is reflected in the value of the Gross Regional DomesticProduct (GRDP) of an area / region. Distribution of funding performed Islamic banking is givenbased on the purpose and use of the funds are classified into financing for working capital,investment and consumption. This research was to determine (1) the effect of the growth ofworking capital financing (MK), investment (I), and consumption in Islamic commercial bankingon growth GRDP West Kalimantan. (2) Determine which variables are the most dominantinfluence on GRDP growth in West Kalimantan. Sources of data working capital financing,investment and consumption of Islamic banking statistics obtained from Bank Indonesia whilethe GRDP data from the Central Statistics Agency (BPS) of West Kalimantan. The analyticalmethods used were multiple linear regression with a significance level of 0.05. The results of thisresearch indicate that (1) the growth of working capital financing, investment and consumptionin Islamic commercial banking simultaneously the effect on the GRDP growth in WestKalimantan. Partially, on the financing of investment and consumption variables there aresignificant positive effect on GRDP growth West Kalimantan. However, variable financing forworking capital of individual negative and not significant. 2) The most dominant variable effecton the GRDP growth is financing consumption, followed by financing investment and workingcapital. The value of the coefficient of determination Adjusted R2 of 0.489, it means that thefinancing of working capital, investment, and consumption of Islamic commercial banking affectGRDP growth of 48.9 percent. While the rest influenced by other variables not included in thisstudy.